Exploring gender issues associated with wanita/woman and perempuan/woman in Malaysian Parliamentary Debates: a culturomic approach - Jamaluddin Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Language use and function can reveal tremendously about the society. In the context of Malaysian Hansard, parliamentary discourse is useful in understanding how certain issues are discussed, understood and resolved. For this paper, two Malay words wanita/woman and perempuan/woman, both refer to the English equivalent ‘woman’, are used to identify some Malaysian women issues as found in the Malaysian Hansard Corpus (MHC). The objectives of this research are: 1) To identify the frequency of both lexicals wanita/woman and perempuan/woman; 2) To identify the unique trend or pattern of the usage of these two lexical items; 3) To identify some issues related to women based on the trend identified. For that reason, Malaysian Hansard Corpus from Parliament 1 (P1) (year 1959) to Parliament 13 (P13) (year 2018) involving over 157 million words is used. The research employs both quantitative and qualitative research approaches. Culturomics approach and tool (AntCon software), are employed to identify the frequency and the trend by generating n-grams. The qualitative approach involves a discourse analysis of MHC based on the trend shown in the n-grams. The research finds that the nodes wanita/woman and perempuan/woman collocate rather consistently with the word lelaki/man. This means women issues are often compared to men’s conditions and situations. There is also a shift in trend in terms of how wanita/woman and perempuan/woman have been discussed, that is, from women functioning in private sphere (collocates like anak/child and mengandung/pregnant to a more public one (collocates like guru/teacher and gaji/salary). However, there is no apparent shift in terms of women being defined as a biological category (sex) or a cultural category (gender). Cultural connotations of both words influenced the choice of words employed in the discourse that contribute towards our understanding of the changing trend of the way women issues have been discussed.